Cyber Threat to Critical Infracstructure and Defending National Security in Nigeria - Kpae, Gbenemene (International Journal of Economics, Business and Management Studies, 2020)
Cybercrime especially those that threatens critical infrastructures is a growing phenomenon in Nigeria, and posing great danger to the nation’s national security. Prior to this time, cybercrime was limited to advance fee fraud with limited impact on the Nigeria’s national security, however of recent cybercrimes have extended to other critical areas, such as finance, maritime, oil sector, telecommunication, defence etc that are vital for the survival of the nation’s economy and national security. Apart from economic sabotage committed by internet criminals, terrorist organisations and individuals with subversive tendencies have also taken advantage of the weak enforcement of the regulatory framework in Nigeria to commit cybercrime. As many companies including government institutions are becoming digitalized, so cyber criminals are devising ways to attack the nation’s critical infrastructures.. The long term impact of cybercrime on the nation’s critical infrastructure is grave if the government does not take serious steps to tackle the problem. This paper examines the threat posed by cybercrime to Nigeria’s critical infrastructure such as banking, information and telecommunication and national security.